Application of fractal formalism for express analysis of mechanical properties of parts - Yaremenko, O. Y.; Яременко, О. І. (Харківський національний автомобільно-дорожній універститет, 2024)
The method of comparative evaluation of the effectiveness of strengthening technologies for increasing the durability of hydraulic hammer parts by means of detonation spraying is considered. For an express analysis of the mechanical properties of the striker and the peaks of the hydraulic hammer after detonation spraying, the fractal formalism is used to predict the mechanical properties. The fractal dimension of the microstructure was calculated at a magnification of 100.
Застосування фрактального формалізму для експресного аналізу механічних властивостей деталей
Keywords: detonation coating; surface; fractal; strength; hydraulic hammer; mathematical model.; детонаційне покриття; поверхня; фрактал; міцність; гідромолот; математична модель.; 621.793